On the role of inhibition in suppression-induced forgetting - Kevin van Schie; Jonathan M. Fawcett; Michael C. Anderson (Scientific Reports, 2023)
Abstract Suppressing retrieval of unwanted memories can cause forgetting, an outcome often attributed to the recruitment of inhibitory control. This suppression-induced forgetting (SIF) generalizes to different cues used to test the suppressed content (cue-independence), a property taken as consistent with inhibition. But does cue-independent forgetting necessarily imply that a memory has been inhibited? Tomlinson et al. (Proc Natl Acad Sci 106:15588–15593, 2009) reported a surprising finding that pressing a button also led to cue-independent forgetting, which was taken as support for an alternative interference account. Here we investigated the role of inhibition in forgetting due to retrieval suppression and pressing buttons. We modified Tomlinson et al.’s procedure to examine an unusual feature they introduced that may have caused memory inhibition effects in their experiment: the omission of explicit task-cues. When tasks were uncued, we replicated the button-press forgetting effect; but when cued, pressing buttons caused no forgetting. Moreover, button-press forgetting partially reflects output-interference effects at test and not a lasting effect of interference. In contrast, SIF occurred regardless of these procedural changes. Collectively, these findings indicate that simply pressing a button does not induce forgetting, on its own, without confounding factors that introduce inhibition into the task and that inhibition likely underlies SIF.